Reefs and islands of the Chagos Archipelago, Indian Ocean: Why it is the world's largest no-take marine protected area - Sheppard, C; Ateweberhan, M; Bowen, B; Carr, P; Chen, C; Clubbe, C; Craig, M; Ebinghaus, R; Eble, J; Fitzsimmons, N; Gaither, MR; Gan, C; et al. (2012)
The Chagos Archipelago was designated a no-take marine protected area (MPA) in 2010; it covers 550 000km2, with more than 60 000km2 shallow limestone platform and reefs. This has doubled the global cover of such MPAs. It contains 25-50% of the Indian Ocean reef area remaining in excellent condition, as well as the world's largest contiguous undamaged reef area. It has suffered from warming episodes, but after the most severe mortality event of 1998, coral cover was restored after 10years. Coral reef fishes are orders of magnitude more abundant than in other Indian Ocean locations, regardless of whether the latter are fished or protected. Coral diseases are extremely low, and no invasive marine species are known. Genetically, Chagos marine species are part of the Western Indian Ocean, and Chagos serves as a 'stepping-stone' in the ocean. The no-take MPA extends to the 200nm boundary, and. includes 86 unfished seamounts and 243 deep knolls as well as encompassing important pelagic species. On the larger islands, native plants, coconut crabs, bird and turtle colonies were largely destroyed in plantation times, but several smaller islands are in relatively undamaged state. There are now 10 'important bird areas', coconut crab density is high and numbers of green and hawksbill turtles are recovering. Diego Garcia atoll contains a military facility; this atoll contains one Ramsar site and several 'strict nature reserves'. Pollutant monitoring shows it to be the least polluted inhabited atoll in the world. Today, strict environmental regulations are enforced. Shoreline erosion is significant in many places. Its economic cost in the inhabited part of Diego Garcia is very high, but all islands are vulnerable. Chagos is ideally situated for several monitoring programmes, and use is increasingly being made of the archipelago for this purpose. © 2012 John Wiley and Sons, Ltd.